Address delivered at the opening of the Ninth Session of the Society - Longfield, Mountifort (Dublin Statistical Society, 1856)
WE are now entering upon the ninth session of this Society, and the duration of its existence during a period of eight years must be a source of unfeigned gratification to all its members, as of itself affording a sufficient proof of the possibility of uniting Irishmen of all creeds and parties in one common object. Our meetings here have shewn how important subjects may be discussed in perfect harmony by persons sincerely anxious to arrive at truth. As a Statistical Society, our object is to obtain and diffuse a knowledge of facts and figures; or, more strictly speaking, of those facts which are most accurately expressed and compared by means of numbers. It is also the object of this Society to hold discussions on political economy, especially on subjects admitting of statistical illustration.
Read November 19th
Keywords: Dublin Statistical Society; 314.15